PREDICTIVE-ANALYTICAL ASPECTS OF APPROACHES TO THE RESEARCH OF “NEGATIVE” CONTENT IN THE NATIONAL INFORMATION SPACE - Любовець, Г.; Король, В. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2019)
The article deals with the new approaches to realities of the modern information space, emerged by creative and technological communicativecontent aggression of Russia against Ukraine and other free nations. As a result of our research, a draft typology of information space components by dynamically situational models of content streams is proposed. One aspect of Russian communicative-content aggression technologies is poisoning of information space by provocative senses, emphasis, styles, even energy impacts. In this case analyzing of parameters and changes in content streams give us an opportunity to fix and to indicate such kinds of enemy “negative” content creation efforts. Also, it provides necessary conditions for producing effective information countermeasures and communicative-content dominance algorithms. Communicative-content aggression is an integral part of global hybrid terrorism technology of Putin's Russia. So, importance of scientific definition of this phenomenon is proven and basic hypothesis is proposed in the article. Key words: information space, communicative-content aggression, information fields, communicative-content societies, public dominance, global hybrid terrorism.